Integrated model for tourists' intention using Web 3.0 based on Technology Acceptance Model and updated Information Systems Success Model - Albaom, Mohammed Abdo Mohammed (2024)
The rapid revolution of information technology has enhanced the global tourism industry that positively changed the structure of economy in large scale. Today, tourists face difficulties to find information to meet their needs or exceed their expectations due to the huge amount of information in the current web and tourism portals. This has made the tourists or travelers decision to visit a particular destination very difficult. Therefore, despite the enormous transformative innovation that Web 3.0 provides, there is still a significant gap between the current applied systems and the new technology at this moment. Besides that, the literature has shown that there are only few publications that used integrated theoretical model of Technology Acceptance Model (TAM) and Delone and Mclean Information System Model (DMISM) to investigate tourist’s intention to use new technology particularly Web 3.0. The main purpose of this research is to propose a conceptual integrated model to determine the factors influencing tourist’s intentions to use Web 3.0. Besides that, this research is being conducted to address information overload, bridging the gap in literature, understanding the impact of Web 3.0 on tourists’ intention, advancing knowledge and understanding. In addition, this research not only defines Web 3.0, but also determines the possible challenges, risks, and opportunities that emerged from Web 3.0 technology specifically in the tourism domain. Furthermore, this study provides an overview of the application of the Web 3.0 in the tourism and how Web 3.0 will provide a great benefit to both the tourism organizations and tourists as this research issue has not investigated and enriched well in the literature. Moreover, while Web 3.0 is prominent across businesses, there is surprisingly very limited academic work devoted to study its effect on consumer’s intentions to use and the tourism industry is not an exception. Besides that, the integrated model of this study was empirically tested using questionnaire survey as the data collected from 643 participants and the subsequent analysis employed structural equation modelling (SEM) via SmartPLS 3.3.3. The results revealed that perceived usefulness, perceived ease of use, information quality, system quality, service quality, computer selfefficacy, social influence, perceived privacy risk, and personal innovativeness are positively associated with tourists' intention to use Web 3.0. While awareness is negatively associated with tourists' intention to use Web 3.0. As a result, this research offers further understanding, enhances insights, and adds value to the expanding field of study. Moreover, the integrated conceptual model proposed can serve as a foundational framework adaptable across various domains for future investigations.